Materialna, ale niesamowita. Elektroniczna muzyka Andrzeja Markowskiego i SEPR w filmach fantastycznych - Topolski, Jan (Res Facta Nova, 2022)
The text focuses on three early soundtracks by conductor-composer Andrzej Markowski (1924–1986) for sci-fi films: Milcząca gwiazda (dir. Kurt Maetzig, 1959), Wielka, większa i największa (dir. Anna Sokołowska, 1962) and Przekładaniec (dir. Andrzej Wajda, 1968). Electroacoustic sounds were created with the help of engineers Eugeniusz Rudnik and Krzysztof Szlifirski in the Polish Radio Experimental Studio. Very physical methods and means of their production contributed greatly to the potential of embodying unreal worlds and objects. The simultaneous birth of musical avant-garde and sci-fi cinema in Poland led to the cliché of illustrating these films with electroacoustic sounds, which produce the experience of „uncanniness" in the audience. A brief portrait of Markowski and a history of his film music output are then presented in a methodological framework, relying mainly on Michel Chion's notion of rendering. In the analyses that follow much space is dedicated to the comparison between sounds in the original novels (Stanisław Lem’s Astronauts and Jerzy Broszkiewicz’s Wielka, większa i największa) and their film adaptations. In the crucial scenes from Milcząca gwiazda the mysterious “reel” from Venus is musically decrypted in a laboratory; the “insect” probes’ tones embody liveliness and multitude, and the gurgling of “lava” causes ambiguous reactions. In Wielka, większa i największa the sound effects of spaceship, soundscape of Vega planet and modulated voices or concrete sounds create the affect of Uncanny (Ernst Jentsch). Eventually, in Przekładaniec electroacoustic music is associated with madness or illness, as happened in many other films from that time. However, Markowski’s innovative use of acoustic and electronic music made these three particularly remarkable.